2013
DOI: 10.1093/aob/mct004
|View full text |Cite
|
Sign up to set email alerts
|

trnL-F is a powerful marker for DNA identification of field vittarioid gametophytes (Pteridaceae)

Abstract: This study demonstrates that DNA barcoding (i.e. reference databasing, tissue-direct PCR and molecular analysis), especially the trnL-F region, is an efficient tool to identify field gametophytes, and has considerable potential in exploring the ecology of fern gametophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…The trnL‐F region showed a high PCR success rate (88.6% %) with only one pair primer and had the longest DNA sequence among the tested loci, which corresponded well with the results of studies carried out on other groups of plants (Chen et al . b; Wong et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The trnL‐F region showed a high PCR success rate (88.6% %) with only one pair primer and had the longest DNA sequence among the tested loci, which corresponded well with the results of studies carried out on other groups of plants (Chen et al . b; Wong et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of the trnL intron is that the most commonly used primer combination (i.e. the c and d primers of Taberlet et al 1991) do not work in at least some ferns (Trewick et al 2002) although alternative primer combinations targeting this region are considered to have potential for exploring fern diversity (Chen et al 2013). Moreover, and perhaps more importantly, Drummond et al (2015) report that when used in soil, the majority of sequences produced by these primers were of prokaryotic origin.…”
Section: Current Practices For the Analysis Of Plant Communities Withmentioning
confidence: 99%
“…Recently, DNA barcoding has been increasingly applied to identify field‐collected fern gametophytes, and has revealed that gametophytes do indeed occur outside of the range of sporophytes in some species (e.g., Chen et al. , Ebihara et al. , Kuo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…, Chen et al. ). Furthermore, the DNA sequences generated by such a study can also be used to infer phylogenetic trees, thus enabling a phylogenetically informed study of community ecology (Kress et al.…”
Section: Introductionmentioning
confidence: 99%